STUDY OF FLOTATION OF Pb-Zn COMPLEX ORE FROM BOGOR AREA BY FROTH FLOTATION AND DIFFERENTIAL FLOTATION METHODS - HASBI FADHILAH (NIM : 12513058), ERZA
Lead (Pb) and zinc (Zn) are non-ferrous metals that are widely used in daily life. Lead is mostly produced from primary source, namely galena (PbS) and mostly associated with sphalerite. Effectiveness in the flotation process is required, such as appropriate collectors and appropriate flotation methods. In this study, we studied the effect of pH on the contact angle of galena, sphalerite and quartz minerals, the effect of pH and collector type on percent of recovery of lead, percent of recovery zinc, grade of lead, grade of zinc, grade of iron, and grade of silica in batch flotation and differential flotation of Pb-Zn complex ore from Bogor. Series of experimental activities began with the preparation of the Pb-Zn complex ore, which includes crushing, grinding, and sieve analysis. Characterization of ore samples was done using X-Ray Diffraction (XRD), X-Ray Fluorescence (XRF), Atomic Absorption Spectroscopy (AAS) and mineragraphy. Then, we measured the contact angle of galena minerals, sphalerite, and quartz. After measurement of contact angle, flotation experiment was performed with pH slurry variable (pH 5,8,9,11 and 12), collector type (Potassium Amyl Xanthate, Sodium Isobutyl Xanthate and Ammonium Alkyl Dithiophosphate), and flotation methods (froth flotation and differential flotation). The result of the measurement of the contact angle shows the result of galena and sphalerite being hydrophobic by the interaction with each collector, while the quartz remains hydrophilic. The grades of Pb-Zn and recovery values on PAX and SIBX collectors do not make a significant difference. The dithiophosphate collector provides lower grade results than the xanthate collector. Galena flotation achieved optimum results at pH 9 with PAX collector with Pb content of 18.47% and 98.32% revovery on differential method. Sphalerite flotation achieves optimum results at pH 12 with PAX collector with Zn content of 52.24%. The results showed that the differential flotation method on the Pb-Zn complex ore produced better grade and recovery concentrates than the froth flotation method.